ANALISIS KEPADATAN TANAH PADA RUAS JALAN MASUK KEMAKAM GURU CANTUNG KECAMATAN KELUMPANG HULU KABUPATEN KOTABARU - Dina Heldita (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
Support for highway planning that must be determined according to the optimal traffic requirements for traffic that is in accordance with its function. Analysis of soil density on the Banian-Sungai Durian road uses a Dynamic Cone Penetrometer (DCP) tool with the aim of finding the CBR value of the soil. The value supported is to get the DCP value, the California Bearing Ratio (CBR) value, and the Land Carrying Capacity (DDT) value. Tests carried out along the 1,550 m with a width of 4m. For the point of data collection zigzag per 100 m. The test results show the average value of DCP is 29.32 mm, while the average value of CBR is 5.07%. Design CBR value is 2.24%, with DDT is 4.47%. The CBR value of the design obtained does not meet the standard CBR value requirements that have been set at 6%. It needs to be re-compacted on the ground because it does not meet the CBR value standards that have been determined and approved to add road pavement.Keywords: Land density, DCP, Field CBR, Banian Village